Optimizing Production Cost through Activity-Based Costing Approach as a Strategy to Increase Company Profit - Arlan Tahir; Iriana Auliyah; Adriani Lande; Siti Mariani Basannang (Jurnal Economic Resource, 2026)
This study aims to conduct a comprehensive mapping of the effectiveness of Activity-Based Costing (ABC) in improving the accuracy of cost determination and company profitability, and to identify the factors that influence its implementation and its contribution to managerial decision-making. This study uses a Systematic Literature Review (SLR) approach to 35 scientific articles published between 2018 and 2025 from accredited databases. The synthesis process was carried out through a thematic analysis of the application context, implementation results, and the mechanisms underlying the relationships among ABC, cost accuracy, and profitability across industry sectors. The results show that ABC consistently improves cost accuracy, operational efficiency, and the quality of managerial decision-making. The success of implementation depends heavily on organizational readiness, information technology support, and human resource capacity. In addition, integrating ABC with digital systems and sustainability reporting further enhances its strategic role in modern cost management. Practically, this research confirms that ABC is worth implementing as a cost management strategy that supports organizational profitability and sustainability. Scientifically, this study strengthens managerial accounting theory by offering an integrative model that explains the mechanism of ABC's effectiveness in the context of digital transformation and modern governance.